Common fixed point theorems in 2 non-Archimedean Menger PM-space - Renu Chugh; Sumitra (International Journal of Mathematics and Mathematical Sciences)
We introduce the concept of a 2 non-Archimedean Menger PM-space and prove a common fixed point theorem for weak compatible mappings of type (A).